2019
DOI: 10.1002/1873-3468.13448
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatically oxidized arachidonic acid regulates T‐type Ca2+ currents in mouse spermatogenic cells

Abstract: During spermatogenesis, fatty acids play an important role both as structural components and messengers that trigger male germ cell line differentiation. The spontaneous oxidation of fatty acids causes a decrease in mammalian fertility. Here, we examine the effects of nonenzymatically oxidized arachidonic acid (AAox) on mouse spermatogenic T‐type Ca2+ currents (ICaT) due to their physiological relevance during spermatogenesis. AAox is 25‐fold more potent than AA at inhibiting ICaT and it left shifts the I‐V cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that AA metabolites affect the transmission of synaptic signals mainly through the G protein‐coupled receptors (GPCRs) cannabiniod receptors (CB1 and CB2), which are highly expressed in the hippocampus, basal ganglia, cerebellum, cortex, thalamus, amygdala, and olfactory bulb. Furthermore, non‐GPCR molecular targets of AA metabolites have been discovered, such as the membrane cation channels known as TWIK‐related acid‐sensitive K (TASK‐1 K + ) channels, T‐type Ca 2+ channels, and vanilloid type 1 receptor (VR1) 95–97 . In long‐term depression state, postsynaptic IP3 receptor‐mediated Ca 2+ release from internal stores, postsynaptic eicosanoids synthesis, and activation of CB1 receptors possibly via release of the gliotransmitter d‐serine 98 .…”
Section: Aa Metabolism In Human Health and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that AA metabolites affect the transmission of synaptic signals mainly through the G protein‐coupled receptors (GPCRs) cannabiniod receptors (CB1 and CB2), which are highly expressed in the hippocampus, basal ganglia, cerebellum, cortex, thalamus, amygdala, and olfactory bulb. Furthermore, non‐GPCR molecular targets of AA metabolites have been discovered, such as the membrane cation channels known as TWIK‐related acid‐sensitive K (TASK‐1 K + ) channels, T‐type Ca 2+ channels, and vanilloid type 1 receptor (VR1) 95–97 . In long‐term depression state, postsynaptic IP3 receptor‐mediated Ca 2+ release from internal stores, postsynaptic eicosanoids synthesis, and activation of CB1 receptors possibly via release of the gliotransmitter d‐serine 98 .…”
Section: Aa Metabolism In Human Health and Diseasesmentioning
confidence: 99%
“…Furthermore, non‐GPCR molecular targets of AA metabolites have been discovered, such as the membrane cation channels known as TWIK‐related acid‐sensitive K (TASK‐1 K + ) channels, T‐type Ca 2+ channels, and vanilloid type 1 receptor (VR1). 95 , 96 , 97 In long‐term depression state, postsynaptic IP3 receptor‐mediated Ca 2+ release from internal stores, postsynaptic eicosanoids synthesis, and activation of CB1 receptors possibly via release of the gliotransmitter d‐serine. 98 Notably, the underlying mechanism of AA metabolites regulation of Ca 2+ influx between neuron synapses may rely on reduced N‐methyl‐D‐aspartic acid receptor (NMDAR)‐induced calcium influx via CB1‐mediated closure of voltage‐sensitive calcium channels in the brain (Figure 3 ).…”
Section: Aa Metabolism In Human Health and Diseasesmentioning
confidence: 99%